Dysphagia Days as an Assessment of Clinical Treatment Outcome in Eosinophilic Esophagitis. (20th December 2022) - Hirano, Ikuo; Rothenberg, Marc E.; Zhang, Sandra; de Oliveira, Claudia; Charriez, Christina M.; Coyne, Karin S.; Bacci, Elizabeth Dansie; Dellon, Evan S.
Abstract : INTRODUCTION: The aim of this study was to evaluate Dysphagia Days as a measure of symptom improvement in patients with eosinophilic esophagitis from the HEROES study. METHODS: Dysphagia Days, defined as a yes answer to the following question: During any meal today, did food go down slowly or get stuck in your throat or chest? was assessed for cendakimab vs placebo. RESULTS: A statistically significant reduction in the mean number of Dysphagia Days experienced was observed with cendakimab 360 mg vs placebo at week 16 (−4.67 vs −1.83; P = 0.0115); an even greater improvement was observed in steroid-refractory patients vs placebo (−4.48 vs −0.04; P = 0.0079). DISCUSSION: Dysphagia Days represents a relevant clinical end point to capture dysphagia-related symptoms.